Cell‐free next‐generation sequencing impacts diagnosis and antimicrobial therapy in immunocompromised hosts: A retrospective study. Issue 1 (11th January 2023) - Vissichelli, Nicole C.; Morales, Megan K.; Kolipakkam, Bharadhwaj; Bryson, Alexandra; Sabo, Roy T.; Toor, Amir A.
Abstract: Background: Cell‐free next‐generation sequencing (cfNGS) may have a unique role in the diagnosis of infectious complications in immunocompromised hosts. The rapid turnaround time and non‐invasive nature make it a promising supplement to standard of care. Methods: This retrospective, observational single‐center study at a tertiary care medical center in Virginia investigated the use of cfNGS in clinical practice. Patients over age 18 years with cfNGS performed for any indication were included. The primary outcome was detection of bacteria and/or fungi on cfNGS. The secondary outcomes were concordance, and abundance of fungal and bacterial organism concentration detected over time from symptom onset, and clinical impact. Results: Thirty‐six patients (92% immunosuppressed) were identified and included. Twenty‐one (58%) tests detected one to five organisms (14/21 bacteria, 8/21 fungi, and 6/21 viruses). The clinical impact of cfNGS was positive in 52.8% of cases, negative in 2.8%, and negligible in 44.4%. Positive tests prompted therapy changes in 12 of 21 patients; six of 20 bacteria and seven of eight fungi identified were considered clinically pathogenic. Three bacteria identifications and six fungi identifications prompted targeted treatment. When fungal species were not identified by cNFGS, antifungal de‐escalation occurred in seven patients. Conclusion: cfNGS assisted in critical management changes, including initiation of treatment for identified organisms and antimicrobial de‐escalation. Its non‐invasive nature and rapid turnaround time make this an important adjunct to standard of care testing that may assist in providing earlier, targeted therapy, especially when opportunistic pathogens remain high on the differential diagnosis. Abstract :